Perancangan Aplikasi Transportasi Online di Kota Ketapang Menggunakan Pendekatan User Centered Design - Kevin Kevin (Politeknik Bisnis Indonesia, 2022)
Online transportation application has been one of the most essential utility in this modern life. This application is very important for the majority of the student and also a healthy percentage of the workers in Indonesia. This is caused by several aspects such as unavailability of personal vehicle and the convenience of online food delivery. Online transportation application has been around for the past 12 years in big cities in Indonesia, however this service is not available in one of the city in West Kalimantan named Ketapang. Ketapang is slowly improving from its past years with the appearance of various famous companies and school. Because of the things mentioned before, the demand for an online transportation application has been increasing and it will be a big help if there’s an application that gives those services with a suitable user interface and user experience with most of the people in Ketapang. This research uses the User-centered Design (UCD) method that prioritizes in giving the best experience the user can have while using the application.